Transcriptomic reprogramming and epigenetic regulation underlying pollination-dependent and auxin-induced fruit set in tomato - Li, Xiaohan; He, Bing; Djari, Anis; Frasse, Pierre; Maza, Elie; Regad, Farid; Pirrello, Julien; Hu, Guojian; Bouzayen, Mondher (Frontiers in Plant Science, 2025)
The transition from flower to fruit, naturally triggered by flower pollination and known as fruit set, is instrumental for plant reproduction, seed formation, and crop yield. Notably, this developmental process can also proceed in the absence of flower fertilization, although it remains unclear whether pollination-dependent and pollination-independent fruit sets undergo similar transcriptomic reprogramming. Genome-wide transcriptomic profiling of the flower-to-fruit transition, either pollination-induced or triggered by auxin treatment, shows that both types of triggers modulate the expression of a common large set of genes primarily expressed in maternal tissues. These include genes related to auxin, gibberellin, brassinosteroid, and ethylene signaling. Furthermore, analysis of changes in histone marking during this transition phase indicated that gene reprogramming underlying both types of fruit set primarily correlated with dynamic changes in H3K9ac and H3K4me3 histone marks. Notably, MCM1, AG, DEFA and SRF (MADS)-box and NAM, ATAF1/2, and CUC2 (NAC) genes were extensively downregulated during the transition from flower to fruit, suggesting their negative roles in fruit initiation. In contrast, Teosinte branched1/Cincinnata/proliferating cell factor (TCP), SQUAMOSA -promoter binding proteins (SBP), Sucrose nonfermenting 2 (SNF2), Growth-regulating factor (GRF), and Su (var)3-9, Enhancer-of-zeste and Trithorax (SET) family genes were significantly upregulated in both pollinated and auxin-treated young developing fruits, suggesting their active roles in promoting fruit sets. Despite these similarities, a comparative analysis of the effects of natural pollination and auxin treatment revealed several differences, primarily related to seed development and hormone signaling. Taken together, the data support the idea that auxin serves as the central hormone orchestrating the extensive gene reprogramming associated with fruit initiation in tomato.